Epidemiology and course features of acute kidney injury in Ukrainian children - O. Lavrenchuk; S. Fomina; G. Suslova; I. Bagdasarova (Ukrainian Journal of Nephrology and Dialysis, 2022)
Abstract. Epidemiological or clinical study on the pediatric population has not been conducted in Ukraine since the term acute kidney injury (AKI) was defined in the year 2004. Our study aimed to analyze the epidemiology, etiology, and features of the AKI in children over 20 years period.Materials and methods. The study included 242 children aged 6 months to 18 years with AKI who were observed during the years 2002-2020 in the reference center (until the year 2002: n=17; 2002-2012 years: n=105; 2013-2020 years: n=120).Results. The number of patients per 10.000 children ranged from 0.025 to 0.034 from 2013 to 2017, except for the year 2015 (0.008), but it began to decrease in 2018. Patients from the Kyiv region accounted for one-third of all episodes (34-29%), and the quotas of the Central Ukrainian region were also stable (6-5-4%). The quantity of Podolsky region tripled after the year 2012 (from 6 to 19%), and patients from the Black Sea region and Donetsk region appeared in the structure at that time (15-14% and 13-7%, respectively). The part of the Northwest region of Ukraine was reduced significantly (from 24 to 8%), as the Northeast region (from 12 to 5%) and Carpathian region (from 12 to 3%). Boys predominated among patients (145/59.9%), and the average age at disease onset was 4 years (from 3 months to 17 years and 11 months).The main AKI cause in children aged under the 12 months and 1-3 years old was hemolytic-uremic syndrome (with or without intestinal disorders), its quantity decreased in the age from 3 to 10 years (due to the increasing number of patients with hemolytic anemia) and in adolescents (due to glomerulonephritis and toxic factors). Complications such as multiple organ failure syndromes, sepsis, and congenital anomalies of the kidney and urinary tract aggravated the course of AKI.Conclusions. The relative proportion of AKI cases per year decreased in 2018-2019 compared to the 2013-2017 period with the largest part of disease detection in the central regions of Ukraine. Dominant etiological factors, age differences and complications of AKI in children were identified.